SUPERVISORS’ RATING OF COMPUTER COMPETENCIES POSSESSED BY SECRETARIES FOR EFFECTIVE PERFORMANCE IN THE PUBLIC SERVICE OF ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure effective performance by secretaries in the technology driven eranecessitated this study on supervisors’ rating of computer competencies possessed bysecretaries for effective performance in the public service of Anambra State. Threeresearch questions guided the study and two null hypotheses were tested. Descriptivesurvey design was adopted. A population of 107 supervisors was studied withoutsampling because the population was manageable. A structured questionnaire with 25items in three clusters was used for data collection. The instrument was validated bythree experts and has reliability coefficients of 0.92, 0.92 and 0.93, for the threeclusters respectively. The arithmetic mean and standard deviation were used toanswer the research questions while t-test was used to test the null hypotheses at 0.05level of significance. Findings indicated that computer competencies possessed by thesecretaries in the three areas were rated low. Gender had a significant effect on therespondents’ rating on hardware manipulative competencies and word processingcompetencies but did not significantly affect respondents’ rating on spreadsheetcompetencies possessed by the secretaries. It was concluded that secretaries inAnambra State public service poorly possess computer competencies for effectiveperformance. Based on the findings and conclusion of the study, it was recommendedamong others that secretaries in Anambra State public service should enroll incomputer training programmes to acquire relevant competencies for effectiveperformance in the public service.